What matters to Hong Kong's inbound market? Modeling Hong Kong's tourism demand. Issue 4 (1st October 2016) - Wondirad, Amare; Agyeiwaah, Elizabeth
ABSTRACT: The factors that determine demand of a particular tourism destination is of significance to destination management organizations and businessmen as part of increasing revenues and staying competitive. The purpose of this study is to generate tourism demand models of four outbound tourism market of Hong Kong using general-to-specific modeling procedure. The data are time series covering the period of 1995–2013 meant to give an up-to-date consumer responsiveness to income and price changes at the destination. The study found income, price, word of mouth and external factors as key determinants of Hong Kong tourism. The outcome is useful for private businesses and public organizations in terms of synchronizing themselves in accordance with global and regional changes.